MENDORONG PEREKONOMIAN DESA: MEDIA PROMOSI DIGITAL SEBAGAI PENDORONG PENJUALAN PRODUK STICK UDANG KELOMPOK MENTARI DESA SUNGAI KUPAH - Imansyah, Fitri; Sujana, Ivan; Arsyad, M Iqbal; Gianto, Rudy; Pontia, Trias; Kurnianto, Rudi; Pragestu, Steven (Universitas Mataram, 2024)
Village economic development is a crucial aspect in improving the welfare of rural communities. In Sungai Kupah Village, the Mentari Group has long produced a local product in the form of shrimp sticks which has great potential for development. However, the main challenges faced are the lack of broad market access and lack of knowledge about digital promotional media to increase sales. This community service aims to encourage the economy of Sungai Kupah Village through digital marketing strategies, especially creating a website and online promotion of local products, namely Shrimp Sticks produced by the Mentari Group. Implementation of this strategy is carried out to increase product visibility, increase sales, and empower village communities in the digital economy. The results of this activity recorded a significant increase in sales of Shrimp Stick products, providing a positive impact on the business group's income and the welfare of group members. Empowering village communities in digital skills is one of the important achievements, enabling them to actively participate in the online market. Digital promotional media, including websites and the use of social media, have succeeded in increasing product visibility locally and regionally. By involving the community in the marketing process, strong cooperation and understanding of the importance of the digital economy in the modern era are created. This activity emphasizes the importance of integrating information and communications technology in rural economic development and inspires similar efforts in other communities. The practical implication is that the use of digital promotional media can be a strong driver in strengthening the local economy and improving the welfare of rural communities sustainably.